Respon Tanaman Selada ( Lactuca sativa ) Terhadap Aplikasi Beberapa Konsentrasi Urin Sapi - Haz, Rahmat S; ', Adiwirman; ', Ardian (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aimed to examine the effect of cow urine concentration and obtain the best concentration on the growth of lettuce plants (Latuca sativa). This research has been conducted in the Plant Experiment Unit of the Faculty of Agriculture, University of Riau, District Handsome. This study was performed experimentally using a completely randomized design (CRD) consisting of 5 treatments 3 replications, each experimental unit consisted of 5 plant samples. The treatments were: U0: without giving cow urine, U1: the provision of cow urine as much as 14 ml / liter of water, U2: giving cow urine as much as 19 ml / liter of water, U3: giving cow urine as much as 24 ml / liter of water, U4: giving cow urine as much as 29 ml / liter of water. The parameters measured were plant height, leaf area, leaf number, total plant fresh weight,. The results showed that administration of cow urine was significantly different affected on plant height, leaf number, leaf area, plant fresh weight, consumable weight of lettuce plants. Â  Keyword : Plant Lettuce (Lactuca sativa), Cow Urine